Effects of net efficiency of roller skiing using the diagonal stride on cross-country skiing racing performance - Nakai, A. (Journal of Physical Education and Sport, 2020)
The present study determines net efficiency during roller skiing with the diagonal stride technique and estimates net efficiency at race speed, to determine the relationship between net efficiency and racing performance in cross-country and roller skiing and to evaluate whether net efficiency could be a determinant of racing performance. Eight male collegiate cross-country skiers were assigned to high- and low-level groups (n = 4 each) based on their cross-county skiing performance. Two-dimensional kinematics and oxygen uptake were determined in the skiers while diagonal roller skiing at various speeds on a level track. Net efficiency was calculated from total mechanical work rate comprising the rates of internal and external work and of net energy expenditure. The rates of total mechanical work and net energy expenditure at race speed were estimated by substituting the mean race speed into individual regression equations obtained in the experiment, and net efficiency at race speed was calculated from the estimates. Racing performance in roller and in cross-country skiing is directly associated (r = -.915, p= .001). Net efficiency was higher throughout most of the speed range (p= .029) and at race speed (p = .029) in the high-, than in the low-level group. These findings reveal that net efficiency is one factor in determining racing performance in cross-country and roller skiing, that higher net efficiency enhances racing performance and that the diagonal roller skiing test on flat terrain is possible for assessing performance in cross-country skiers.